'Leaving more than footprints' : modern votive offerings at Chaco Canyon prehistoric site - Arnold, Jeanne E.
A 'heritage manager' who wishes a quiet and an orderly life may hope their heritage place is culturally dead; whatever meaning it once had, now it is an archaeological site, an ancient monument, a tourist attraction. But many sites are not dead. Chaco Canyon, the celebrated complex in the desert of the US Southwest, is of continuing value to Native Americans of its region; and the place has become a focus for New Age ceremony Ñ itself in part inspired by Native American knowledge.